UJI AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN MANGGA BACANG (Mangifera foetida L.)TERHADAP Candida albicans SECARA IN VITRO - ., Ariza Zakiah Imani (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: One of the plants that is often used as medicine are mangoleaves (Mangifera indica). Plant with the same genus that are native toIndonesia is horse mango (Mangifera foetida L.)which expected caninhibit the growth of Candida albicans. Objective: The purpose of thisstudy were to determine the antifungal activity of ethanol extract of M.foetida L. leaves against Candida albicans in vitro, the minimum inhibitoryconcentration (MIC), and the secondary metabolite compounds.Methodology: M. foetida L. leaves were extracted by maceration using70% ethanol. Phytochemical screening test performed on extractsobtained from the maceration. The antifungal activity was determined inthe extracts using Kirby-Bauer Disc Diffusion methods against Candidaalbicans. Ketoconazole 10 Î¼g/ disc was used as positive control whileDMSO ad aqua bidest was used as negative control. Results: Based onthe study result, ethanol extract of M. foetida L. leaves has an antifungalactivity at concentration of 1000; 500; 250; 125 mg/mL, MIC at 125 mg/mLwith zone of inhibition 9,15 mm, phytochemical screening test, containsphenols, flavonoids, tannins, saponins, steroids and alkaloids.Conclusion: Ethanol extract of M. foetida L. leaves has an antifungalactivity against Candida albicans.Keyword: Antifungal, ethanol extract of horse mango leaves, Candidaalbicans